The Antecedents of Celebrity Endorser, Content Marketing and Lifestyle on Purchase Intention - Gusri, Kardandi; Kamener, Dahliana; Irda, Irda; Kamela, Ice; Trianita, Mery (ProBisnis : Jurnal Manajemen, 2024)
The purpose of this study is to analyze the influence of celebrity endorser, content marketing, lifestyle on purchase intention in Bukalapak E-commerce. The case study was conducted in Padang City. The research method is quantitative by using a questionnaire as a data collection instrument. Technique of taking samples was using purposive sampling techniques for sampling obtained 81 respondents. Data was analyzed by using Smart-PLS. The results of this study indicate that the Celebrity Endorser variable has a significant effect on Purchase Intention, Content Marketing has a significant effect on Purchase Intention, And Lifestyle has no effect significantly on Purchase Intention.